Aplikasi Pengenalan Huruf Hiragana dan Katakana Jepang Berbasis Android Menggunakan Kodular - Iwan Setiadi; Santi Widianti; Athaullah Afra Afratofani (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Japan is a country in Asia that has a quite unique culture. There is an influence of Japanese culture on various countries, one of which is Indonesia, such as Anime (Japanese videos and animation), Manga or Japanese comics, and typical Japanese food such as sushi, ramen and takoyaki. This makes many Indonesian people interested in learning Japanese. This Android-based application for recognizing Japanese Hiragana and Katakana letters called